2023
DOI: 10.1111/os.13627
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes and Muscle Invasiveness between Unilateral Biportal Endoscopic Discectomy and Percutaneous Endoscopic Interlaminar Discectomy for Lumbar Disc Herniation at L5/S1 Level

Abstract: Objective Both unilateral biportal endoscopic discectomy (UBED) and percutaneous endoscopic interlaminar discectomy (PEID) could achieve favorable outcomes for lumbar disc herniation (LDH). There are limited studies comparing the two different methods of endoscopic discectomy. The objective was to comprehensively compare the clinical outcome and muscle invasiveness of UBED and PEID for the treatment of LDH at L5/S1 level with at least 1‐year follow‐up. Methods The retrospective cohort study enrolled 106 LDH pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…While muscle-bone separation using the electrical coagulator on the surface of the vertebral lamina, UBED requires a larger range of muscle and soft tissue dissection to obtain greater operating space. Wang L et al [23] indicated the serum CPK level and change rate of lean multi dus crosssectional area (LMCSA) for UBED was obviously higher than PIED at postoperative 1st day. Unlike PIED surgical instruments only used in work channel, various surgical instruments repeatedly enter and exit the surgical area through skin incisions during the operation of UBED, which can easily damage intermuscular blood vessels and cause bleeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While muscle-bone separation using the electrical coagulator on the surface of the vertebral lamina, UBED requires a larger range of muscle and soft tissue dissection to obtain greater operating space. Wang L et al [23] indicated the serum CPK level and change rate of lean multi dus crosssectional area (LMCSA) for UBED was obviously higher than PIED at postoperative 1st day. Unlike PIED surgical instruments only used in work channel, various surgical instruments repeatedly enter and exit the surgical area through skin incisions during the operation of UBED, which can easily damage intermuscular blood vessels and cause bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…From the introduction of UBE technique to its widespread and exible application, it has been proven by many scholars to be safe, effective, and e cient in dealing with cervical, thoracic, lumbar degenerative diseases, and even revision surgery [8][9][10][11] . Although UBE technique provides a broader surgical eld of view and more exible surgical procedures, the accompanying more paraspinal muscle injuries and corresponding hidden blood loss also need to be given su cient attention [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…With the innovation and development of full endoscopic systems [6][7] , spinal endoscopy technology has developed into a safe, effective 8 and e cient 9 alternative to minimally invasive spinal surgery, making it possible for orthopedic surgeons to perform precise decompression surgery through the selection of different approaches 10 . At present, the main minimally invasive endoscopic techniques for the treatment of LDD 11 include percutaneous single-channel interlaminar spinal endoscopy discectomy (PEID) and transforaminal percutaneous endoscopic lumber discectomy,TF-PELD) and unilateral biportal endoscopy (UBE) 12 have been demonstrated in many clinical studies and meta-analyses to be effective and safe [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%